FACTORS INFLUENCING THE NUTRITIONAL STATUS OF UNDER FIVE (1-5 YEARS) CHILDREN IN URBAN-SLUM AREA OF VARANASI - Baranwal, Kavita; Gupta, V M; Mishra, R N; Prakash, Shiv; Pandey, O N (Indian Journal of Community Health, 2010)
Research Question: To study some of the ecological factors in relation to the existing nutritional status of under-five (1-5years,. children in urban-slum area of varanasi. This included the following determinants in particular. Objective: To assess the biological, socio-economic, maternal and dietary factors with nutritional status of under fives children among urban- slum population. Study design: A cross-sectional study Study settings: Deptt. Of PSM, I.M.S., B.H. U, Varanasi Study subject:400 children of underfives age group (1-5years) ofurbanfieldpractice area (Sunderpur community) Study period:July 1999 to July 2000 Study variable : Age, sex, birth order; birth interval, caste of the family, type offamily, literacy status of mother: dietary habit, Colostrum, Exclusive Breast Feeding, Result: A cross-sectional epidemiological study was carried out infield practice area oJthe department of Preventive &Social Medicine, IMS, BHU Among the pre-school children aged 1-5 years the prevalence of PEM as screened out by ‘weight for age’ criteria using “IA P classficcition” was 63.3% . The prevalence was higher in 3rd year age periods as compared to 4th and 5th year During 2nd year of life PEM prevalence was observed to be lowest. Prevalence of PEM in male children was58. 3% as compared to female children (68.6%), the dfference was significant. Among the Socio-econo,nic factors mothers literacy, and caste, were significantly associated with PEM. Children deprived of’ colostrum and exclusive breastfeeding also showed significant dfference in prevalence of PEM.